Effect of Seed Sources on Germination Parameters and Seedling Vigor Index of Oroxylum indicum (L.) Kurtz: OROXYLUM INDICUM SEED SOURCE EFFECT ON SEEDLINGS - Pitamber Singh Negi; Sandeep Sharma; Jawala Prasad; Drishti Sharma; Richa Thakur; Pritika Chauhan; Anita Chauhan (Annals of Arid Zone, 2024)
A germination study was conducted to evaluate the effect of different seed sources on germination parameters and seedling vigor of Oroxylum indicum seeds under laboratory conditions. Significant differences were observed in various germination parameters, moisture content, seed weight, seedling length and seedling vigor index of seeds collected from five different sources in Himachal Pradesh. The maximum germination per cent (100%), mean daily germination (2.17% and 2.08%), peak value (0.67 and 0.63), germination value (1.47 and 1.31), germination speed (3.96 and 3.89), seedling length (6.14 cm and 5.71 cm) and seedling vigor index (614.00 and 571.00) was recorded in seeds collected from the Dhamtal and Jheol seed sources. Like wise the minimum germination per cent (87.25%), mean daily germination (1.74%), peak value (0.60), germination value (1.04), Germination speed (3.39), seedling length (4.76 cm) and seedling vigor index (415.31) was recorded in seeds collected from the Behran seed source. The maximum moisture content (7.02%) was recorded in seeds collected from Behran whereas the minimum moisture content (5.93%) was recorded in seeds collected from the Jalari seed source. The maximum value of 100 seed weight (8.50 g) was recorded in seeds collected from the Dhamtal whereas the minimum value of 100 seed weight (8.23 g) seeds was recorded in seeds collected from the Behran seed source. Similarly, a maximum seedling length (6.14 cm) and seedling vigor index (614.00) were also recorded in seeds collected from Dhamtal whereas a minimum seedling length (4.76 cm) and seedling vigor index (415.31) was recorded from seeds collected from the Behran seed source. The present investigation revealed that the seeds of O. indicum collected from the Dhamtal and Jheol seed source in the Kangra district can be used for better germination and raising nursery stock for its plantation in the lower belt of Himachal Pradesh.